ANALISIS PENGARUH PANDEMI COVID – 19 TERHADAP FINANCIAL DISTRESS PERUSAHAAN JASA DENGAN METODE ALTMAN Z-SCORE ( Studi Empiris Pada Perusahaan Perhotelan Restoran, Dan Pariwisata Yang Terdaftar Di Bursa Efek Indonesia Periode 2018 – 2021) - Andhiny, Andhiny; Sitorus, Eduward Tony; Napitupulu , Rina Dameria (CV. Era Digital Nusantara, 2022)
This study focuses on how the impact of the COVID-19 pandemic on service companies (empirical studies on hotel, restaurant and tourism companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. The method used is the altman zscore analysis method, by analyzing the company's financial statements The population in this study is all service and hospitality companies that have Initial Public Offering (IPO) on the Indonesia Stock Exchange at least since 2018 and below, with a sample of 20 service companies in the hotel, restaurant and tourism subsector. hotel, restaurant and tourism sub-sector services.